Saving Dan Investasi Dalam Produk Mudharabah Pada Lembaga Keuangan Syariah Analisis Komparatif Dengan Produk Konvensional - Kasih, Santi Yulia; Fahlefi, Rizal (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to determine the application of saving and investment inIslamic financial institutions and their comparison with conventional institutions. The method used in this research is qualitative research with an in-depth interview approach. In-depth interview approach. The results showed that saving products at LKS. LKS offers mudharabah savings, wadiah savings, and sharia current accounts with profits for customers calculated based on the profit-sharing ratio proportionally from the profit-sharing ratio. proportionally from bank's operating profit in accordance with the initial agreement. While in LKK the products offered are products offered are savings, deposits, and current accounts with benefits for customers calculated based on the interest rate determined by the bank. Investment products at LKS offer suku', shares, and musyarakah with profits derived from profit sharing, company profits and asset rents. asset rent. Investment products in LKK offer mutual funds, stocks, and bonds with customer profits derived from rising asset prices, dividends and interest.┬á